Oil palm empty fruit bunch carbonization in pilot scale and industrial scale horizontal rotary drums - Lau, Lek Hang (2016)
Oil palm empty fruit bunch, EFB, is one of the biomass wastes generated from the palm oil production industry. Currently most of the EFB are incinerated or utilized as the boiler fuels for steam and electricity generation, some are mulched or composted naturally in the plantation; however these processes generally aggravated environmental problems due to process inefficiency. EFB conversion to biochar is a promising way to resolve the EFB disposal issue, as it is a renewable energy and a carbon neutral cycle if to be used as fuel, contributing in mitigating climate change. The objective of this study is to obtain optimum carbonization conditions of EFB in a horizontal rotary drum towards the char yield and properties. Carbonization conditions to be included are final carbonization temperature and retention time of carbonization. EFB was characterized in laboratory of its elementary composition and moisture content by using CHNS/O-932 analyser and themogravimetry analyser. The results were comparable with previous works. Laboratory thermogravimetry analysis of EFB at 10oC/min, 30oC/min and 50oC/min heating rates using TGA analyser has shown that the maximum decomposition temperatures at different heating rates were in the range of 360oC to 370oC, suggesting good char yield with reasonable preserved calorific values could be produced at carbonization temperature above 370oC. EFB was then carbonized in pilot rotary horizontal drum reactor developed by Nasmech Technology Sdn Bhd at 400oC, 500oC and 600oC with 2.5 hours, 3.0 hours and 3.5 hours retention times and char products from different batch of tests were tested for proximate analysis and calorific values. The EFB char yields are in the range of 21.8% to 26.4%, increase with lower carbonization temperature but no significant effect with retention time. Both carbonization temperature and retention time have no significant effect on calorific value of chars which were at the range of 21.50 MJ/kg to 23.98 MJ/kg. The higher carbonization temperature reduced volatile content and increasing fixed carbon content of char. Retention time has no significant effect towards the char proximate composition EFB char carbonization in 20 T/Day industrial scale rotary drum reactor, developed by Nasmech Technology Sdn Bhd has been performed at 350oC and 400oC final carbonization temperature at 5 hours retention time. The analysis on char product have shown the EFB char produced possessed 22.71 MJ/kJ average calorific value for 400oC char, similar quality with pilot scale char product at same 400oC condition but higher char calorific value of 24.43 MJ/kg was produced at 350oC. This concludes that the char quality is greatly affected by final carbonization temperature and not much by retention time under isotherm final carbonization temperature condition. Yield of Dengkil plant are at average of 22.23% for 400oC char and 25.12% for 350oC char. Dengkil char is classified as medium quality fuel in the rank of bituminous or subbituminous equivalent quality according to ASTM D388 standard classification method for coal, Specific carbonization energy of EFB and heat transfer flux rate through feedstock contact area with reactor drum surface could be used as preliminary scale up criteria of horizontal rotary drum. However the accuracy of upscale rules could be enhanced with further study and incorporation of others heat transfer parameters. Several operational hiccups have been reported for the Dengkil plant for future improvement and to minimize operational downtime of similar reactor system. Despite those shortfalls, the economics and energy balance of EFB char carbonization plant in Dengkil has also been studied by others and concluded that this plant is technical feasible and economically viable with net energy yield of EFB char produced at 11.47 MJ/kg EFB. From this study, optimum EFB char yield and quality is best produced at 350oC to 400oC with 5 hours retention time in the industrial scale horizontal rotary drum carbonization reactor.